Single-Phase Switched-Capacitor 21-Level Inverter Topology Using Reduced Number of Components With High Voltage Gain - Fatemeh Esmaeili; Hamid Reza Koofigar (IEEE Access)
This paper introduces a novel 21-level single-phase inverter based on switched-capacitor (SC) technology, featuring a reduced number of components and input DC voltage supply. The inverter is designed to operate with just one DC source to generate multiple voltage levels. Compared to recently developed SC-based multilevel inverter topologies, the proposed design offers several advantages, including (1) a lower number of semiconductor devices, (2) a higher output voltage gain, (3) self-balancing of capacitors, and (4) reduced voltage stress on the switches. Finally, computer simulations and laboratory tests were conducted to validate the performance of the proposed inverter.